If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -6 = 3x + 6 Reorder the terms: -6 + 9x = 3x + 6 Reorder the terms: -6 + 9x = 6 + 3x Solving -6 + 9x = 6 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -6 + 9x + -3x = 6 + 3x + -3x Combine like terms: 9x + -3x = 6x -6 + 6x = 6 + 3x + -3x Combine like terms: 3x + -3x = 0 -6 + 6x = 6 + 0 -6 + 6x = 6 Add '6' to each side of the equation. -6 + 6 + 6x = 6 + 6 Combine like terms: -6 + 6 = 0 0 + 6x = 6 + 6 6x = 6 + 6 Combine like terms: 6 + 6 = 12 6x = 12 Divide each side by '6'. x = 2 Simplifying x = 2
| -b=19 | | 6-3x=-5x-2 | | 2x-3x=3-x | | a-16/18=8/9 | | 1/6(5x-9)=7 | | 7-x=6+14 | | 8-4=x+1 | | 6x+4x=10 | | y=x^2*ln(x+2) | | 15x+3y=39 | | 1200=0.18*x | | 1200=0.18x | | -3/4+3/2-2 | | -3x-3x=48-6 | | t^2+7t-18=T+1 | | -19.95-1.10x=-2.35 | | f(x)=3x^3-4x^2 | | 2x^2-5x-38=0 | | y=-2(x-3)+4 | | (2x-5)=1 | | 5/6x=30 | | 7x-1=8x-4 | | 3(2x-3)+5=17 | | 3x+8=8x-22 | | -13-x=-5 | | -5.00-4.00x=53.00 | | 3(x-1)-2(x+4)=10 | | -135-20(x-4)=24x | | 6y^4-12y^3+4y^2= | | 4-x=5x+10 | | -65+7(x+7)=-3-4(x-5) | | -6(x+7)=20 |